Khalwat (Close Proximity) Among Youngsters in Malaysia and Aceh: A Study Concerning Shariah Compliance: (Khalwat dalam Kalangan Remaja di Malaysia dan Aceh: Kajian terhadap Pematuhan Syariah) (Kanun: Jurnal Undang-undang Malaysia, 2015)
The commission of khalwat (close proximity) by teenagers has become increasingly worrisome nowadays not only in Malaysia but also in Indonesia. News on the arrest of teenagers by the authorities frequently appears in the daily newspapers and reports. If such acts are not immediately controlled or effectively overcome, it will result in moral collapse in future generations. This article seeks to analyse the concept of teen-age, the offence of khalwat under both the shari'ah and legal provisions of the two jurisdictions, as well as to examine the extent of shari'ah-compliance of these two provisions. This study is a qualitative research where data collection is done via library research and interviews. The data was obtained from related legal provisions, primarily the shari'ah criminal offences enactments of Malaysia and Qanun Syariah Aceh, the Holy Quran, al-Hadith (the sayings of the Prophet), books, journals, newspapers articles, conference proceedings, and the print and electronic media of both countries, as well as interviews conducted with a few prominent persons in the legal and religious fields of both countries. The research finds that shari'ah principles have not been totally complied with and therefore suggests recommendations for the fulfillment fo shari'ah requirements.Keywords: khalwat, shariah offence, teenagers, Malaysia, Aceh